Digital Marketing as a Strategy to Improve Higher Education Promotion During the COVID-19 Pandemic - Rawat, Bhupesh; Sunarya, Po Abas; Devana, Viola Tashya (Startupreneur Business Digital (SABDA Journal), 2022)
In the realm of business, one of the most crucial components in establishing a company's success is promotion. As a result, producers will engage in various sorts of promotions, which will be costly. It's not only promotion from one individual to the next. Social media is now frequently employed as a digital marketing approach. Universities recruit students in the same way that businesses do. Promotions are run to boost the number of prospective students who apply to the college. The education sector in Indonesia will be virtually completely crippled by the year 2020. The government is urging the entire community to exercise physical distance in the middle of the COVID-19 outbreak, which is causing great concern among Indonesia's entire population. Universities all around Indonesia are having difficulty operating as a result of this. Almost all colleges have implemented work-from-home policies, which impede academic and non-academic activities and prevent new students from enrolling. The COVID-19 pandemic has resulted in a significant reduction in the number of potential students enrolling at universities. Universities have a hard time promoting and introducing themselves to the general population. Universities can use digital marketing media to promote higher education as one solution. The purpose of this study is to conceptually examine digital marketing strategies to Improve Higher Education Promotion. The research method used is descriptive research. The findings of this study indicate that social media materials play a major role.